Six senses while considering hydatid cyst as a differential for a swelling at nape of the neck: a case report - Gupta, Shubham K.; Shrivastava, Aviral; Kumari, Sweety; Khanna, Rahul; Meena, Ram N.; Mishra, Shashi P.; Yadav, Harikesh (International Journal of Research in Medical Sciences, 2023)
While cervical swellings usually are located in anterior midline like thyroglossal cyst, thyroid swellings, or in antero-lateral aspect of neck like cold abscess, branchial cyst, lymphangioma, cervical lymphadenopathy etc. Nape of the neck swelling is even less common with differentials including lipoma, sebaceous cyst, lymphangioma, etc. Hydatid cyst (HC) is often missed as a differential resulting in intraoperative surprises. This case report might change the mind of the readers to keep HC in back of their minds while approaching a case of swelling of the neck. Here we report a case of 15 years’ female who presented with swelling of nape of neck which on evaluation was inclining towards lipoma/epidermal cyst. With an intention for surgical exploration and excision, the patient was taken for operation, where we discovered it to be HC and the same was later confirmed by histopathology as well. Because of its rare presentation the primary diagnosis of HC is often missed out in spite of having sensitive cytology and imaging modalities. Hence, by reporting this case we intend to emphasize six facts a clinician, a radiologist and also a pathologist must consider while keeping primary HC at an unusual site as a differential diagnosis.